Inhibitory protection as an instrument for effectiveness of the right to access justice in pandemic times - PAGGIATTO CAMACHO, Luciana da Silva; GRANADO, Daniel Willian; ARÉVALO, Jorge Alfredo; MARTINS, José Alberto Monteiro (Revista de Direito Internacional e Globalização Econômica, 2022)
Object: the purpose of this scientific article is to address the exceptional scenario imposed by the pandemic resulting from the SarsCov2 - COVID-19 virus and its consequences which result in changes in the lives of citizens in relation to personality rights, such as, for example, freedom to go and come, right to information, consumer right, between others, in confrontation with collective rights to safeguard health, as a fundamental good of society as one of the elements that integrate the State: the territory, the sovereignty and the people (perhaps alive). Methodology: the research methodology used is legal-theoretical, through empirical-deductive reasoning through the observation of social reality, studies of the legal system, doctrinal bibliographic material and jurisprudence. Results: the results obtained are respectively (i) the need for reflection and the promotion of constitutional norms to safeguard the Democratic Rule of Law provided in the Constitution; (ii) the defense of the rights and guarantees of the individual, (iii) personality rights and others referenced; (iv) the use of individual inhibitory protections, and (v) collective injunctions to achieve this objective. Finally, in summary, it was concluded that inhibitory protection is an effective means of making rights effective, especially in the exceptional context imposed by the pandemic. Contributions: the intended scientific contribution is initially to stimulate the debate about means of effective judicial protection in the defense of rights, material, diffuse, collective and homogeneous individuals, which are not possible to quantify the damages, in case they are injured, due to their immanent non-patrimonial characteristics, and, in a second moment, to review institutes of procedural law, such as preventive protection, and, in particular, the inhibitory protection, treated here, as a means of safeguarding these rights. Keywords: Inhibitory protection. Right of action. Differentiated jurisdictional protection. Pandemi.